Swahili Made Easy : a Beginner's Complete Course. - Safari, J. F. (Mkuki na Nyota Publishers, 2012)
This handy book is a beginner's complete course in the Swahili language, designed especially for foreigners. The book is a result of the author's many years of teaching experience. It is divided into two parts: part one covers pronunciation; Swahili greetings and manners; classification of nouns; adjectives, verbs, adverbs, etc. in twenty-eight lessons and thirty-six exercises. part two includes a study of Swahili usage in specific situations (e.g. at home, in the market, on the road, at the airport, etc.); eleven further lessons and thirteen exercises; the key to the exercises in Parts One an.